In vivo morphological alterations of TAMs during KCa3.1 inhibition—by using in vivo two-photon time-lapse technology - Massenzio, Francesca; Cambiaghi, Marco; Marchiotto, Federica; Boriero, Diana; Limatola, Cristina; D’Alessandro, Giuseppina; Buffelli, Mario (Frontiers in Cellular Neuroscience, 2022)
Tumor associated macrophages (TAMs) are the mostprevalent cells recruited in the tumor microenvironment (TME). Once recruited, TAMs acquire a pro-tumor phenotype characterized by a typical morphology: ameboid in the tumor core and with larger soma and thick branches in the tumor periphery. Targeting TAMs by reverting them to an anti-tumor phenotype is a promising strategy for cancer immunotherapy. Taking advantage of Cx3cr1GFP/WT heterozygous mice implanted with murine glioma GL261-RFP cells we investigated the role of Ca2+-activated K+ channel (KCa3.1) on the phenotypic shift of TAMs at the late stage of glioma growth through in vivo two-photon imaging. We demonstrated that TAMs respond promptly to KCa3.1 inhibition using a selective inhibitor of the channel (TRAM-34) in a time-dependent manner by boosting ramified projections attributable to a less hypertrophic phenotype in the tumor core. We also revealed a selective effect of drug treatment by reducing both glioma cells and TAMs in the tumor core with no interference with surrounding cells. Taken together, our data indicate a TRAM-34-dependent progressive morphological transformation of TAMs toward a ramified and anti-tumor phenotype, suggesting that the timing of KCa3.1 inhibition is a key point to allow beneficial effects on TAMs.